Chemical, physiochemical and antifungal activity’s assessment of Bauhinia variegata L. (fabaceae) - Filho, Antonio Carlos Pereira de Menezes; Filho, Josemar Gonçalves de Oliveira [UNESP]; da Cruz, Rafael Martins; da Silva, Adrielle Pereira; de Sousa, Wendel Cruvinel; Castro, Carlos Frederico de Souza (My University, 2020)
Introduction: Bauhinia genre is currently represented by around 300 species distributed all over the world, and a number of them with important biological actions in their extracts and essential oils. Objectives: Evaluate the chemical profile, the physicochemical characteristics and the antifungal activity of essential oils extracted from the flowers and fruits of Bauhiniavariegata over Candida genre. Methods: Flowers and fruits were collected in Rio Verde-Goiás, Brazil in the first hours of the morning. The essential oil was extracted by using the Clevenger system. Some physiochemical tests were made as organoleptic characteristics, performance (%), solubility, optical rotation, refraction index and relative density. The antifungal trial was made by using the disk diffusion method and assessing the following stumps: Candidaalbicans, C.krusei, C. tropicalis and C. guilliermondi. Results: It was proved that the essential oils are smooth and aromatic. The chemical profile showed 5 and 6 main compounds from the AEs flower and fruit, respectively. The performance was of 0,37% and 0,66%; the solubility was positive, the optical rotation was of +37,3 and +34,9 α D; the refraction index was of 1,3584 and 1,4601 in 20°C; and the relative density was of 0,937 g mL-1 and 0,931 g mL-1 in 20°C for the flower and the fruit, respectively. The results of the antifungal activity showed through the inhibition zone important results for both essential oils. All the antifungal stumps were sensitive to the assessed oily concentrations. Conclusions: The essential oils of the flower and the fruit of B. variegata show 5 and 6 main compounds, respectively, good physicochemical characteristics and special antifungal activity in comparison with the stumps of Candida.
Evaluación química, fisicoquímica y actividad antifúngica de los aceites esenciales de Bauhinia variegata L. (fabaceae)
Keywords: Antifungal activity; Bauhiniavariegata; Candida; Essential oils´ solubility